"Being a topic expert is not sufficient": a mixed-method analysis of teaching dynamics at the Tasmania police academy. (4th May 2019) - O'Shea, Brianna; Bartkowiak-Théron, Isabelle
ABSTRACT: In unpacking the results of an in-depth longitudinal program evaluation, and in light of literature on police education, we analyse the various elements that contribute to the dynamic delivery of teaching in a police academy. A mixed-method analysis of 5 years of student evaluations enriched with the views of police education managers, coordinators, and educators provides an overview of the circumstances in which educators teach police recruits, the dynamics which unfold when teaching police, and the necessary characteristics for educators when addressing a police audience. This analysis positions the Tasmanian model of police education as an interesting case study in the midst of relatively critical literature about police education, and even more cautious studies on higher education partnerships in policing.